On the reasons of conflict of laws origin - Lysakovskiy, Grigoriy A. (Journal of the Belarusian State University. Law, 2025)
The author of the article analyses such phenomena of law reality as conflict of laws. The reasons of conflict of laws, the base of its classification and chance of its elimination on the law reality are founded.